Devosi Harian sebagai Strategi Pembiasaan dalam Pembentukan Karakter Anak Usia Dini - Eva Hartina Pardede; Hotmaulina Sihotang (Yayasan Darussalam Bengkulu, 2026)
The development of character in early childhood cannot rely solely on incidental learning; it requires consistent habituation that is systematically integrated into daily school activities. This study aims to describe and analyze the implementation of daily devotion activities in shaping early childhood character at School X. This research employed a qualitative approach with a best practice study design. The participants included the principal and teachers of the 5–6-year-old group, selected through purposive sampling. Observational data show that the majority of children (approximately 60–70%) demonstrated a positive tendency in behavioral change in their daily activities. Therefore, daily devotion activities can be regarded as a best practice that supports holistic character development in early childhood education.